Core–shell structured BaTiO3@Al2O3 nanoparticles in polymer composites for dielectric loss suppression and breakdown strength enhancement. (February 2017) - He, Dalong; Wang, Yao; Chen, Xueqin; Deng, Yuan
Abstract: Design of core–shell nanoarchitectures is powerful approach to obtain advanced high- k polymer nanocomposites. Core–shell nanoparticles with uniform amorphous Al2 O3 shell layer encapsulating BaTiO3 (BT) particles were fabricated through an effective, facile and low-cost heterogeneous nucleation method. The dielectric behaviors of the polyvinylidene fluoride (PVDF) nanocomposite films were adjusted by varying BT@Al2 O3 nanoparticles loadings. The effects of Al2 O3 shell and the arising interfaces on the dielectric and electric properties in comparison with bare BT nanoparticles were studied. Due to the highly insulating Al2 O3 shell with proper dielectric constant, the local electric field distribution around interfaces between polar BT nanoparticles and PVDF were greatly modified leading to obvious dielectric loss suppression yet maintaining high dielectric constant. The study provides a solution for obtaining high- k dielectric composite with low loss and high breakdown strength, which is highly desired in high power systems.